DPPH FREE RADICAL SCAVENGER ACTIVITY OF FLAVONOID FROM THE LEAVES OF FERN Chingia sakayensis (Zeiller) Holtt - Suyatno Suyatno; Noor Cholies Zaini; Motoo Tori (Universitas Gadjah Mada, 2005)
A flavonoid compound in flavonol type namely kaemferol was isolated from the ethyl acetate fraction of the methanol extract of the fern Chingia sakayensis (Zeiller) Holtt's leaves. The DPPH free radical scavenger activity of kaemferol was stronger than buthyl hyroxy toluene (BHT) but it was weaker than ascorbic acid (vitamin C) and -tocopherol (vitamin E).